ANALISIS PENGARUH JAM KERJA TERHADAP KINERJA KARYAWAN PASASI DI PT. JASA ANGKASA SEMESTA (JAS) CABANG BANDAR UDARA INTERNASIONAL JUANDA SURABAYA - Adhe Chandra Rushady; Dhiani Dyahjatmayanti (Jurnal Ekonomi dan Bisnis, 2025)
Human resources are crucial for organizational operations and goal achievement, as organizations rely heavily on human contributions. A significant factor influencing organizational success is employee performance. This study aims to evaluate the effect of working hours on employee performance at PT. Jasa Angkasa Semesta (JAS) at Juanda International Airport Surabaya. The research involved 45 employees from the sales department, utilizing questionnaires and literature reviews for data collection. Data analysis was performed through instrument testing, classical assumption testing, hypothesis testing, and simple linear regression using SPSS. The findings indicate that working hours significantly impact employee performance at the JAS branch. The R-Squared value of 0.976 suggests a strong relationship, with the alternative hypothesis accepted, confirming that working hours influence employee performance. The R² value of 97.6% demonstrates a highly significant impact, while the remaining 2.4% is attributed to factors not covered in this study.